Creep feeding para cordeiros com rações farelada ou peletizada - Silva, Tamara Donatti Ferreira da (2010)
It was evaluated the lambs performance feed with mashed or pelleted rations 011 individual or collective creep feeding. There were used 31. males and females '/2 Dorper - Santa Ines, from single birth. The lambs were confined from birth to weaning, receiving a complete ration (20% CP and 80% TDN), being offered from the l4th day on. The lambs were divided into three groups: collective creep feeding receiving mashed feed, coliective creep feeding receiving pelleted feed and an individual creep feeding receiving pelleted diets. The total daily intake of ration in the collective creep feeding, regardless of ration physical form was 48% higher than the consumption in the individual creep feeding. The daily gain increased with the periods of development. The daily weight gain in coliective creep feeding ration was 47.75% higher than the individual creep feeding system. It was calculated the coast of mashed rations of R$ 0,62 and of R$ 0,72 for pelleted feeding. It was estimated the cost per kilogram ofbody weight gain ofthe lamb, being R$ 1,37 for coliective creep feeding pelleted ration and R$ 1,34 for coliective creep feeding and R$ 1,06 for individual creep feeding. Considering the results of weight gain, average daily consumption and cost of feeding for each kilogram of body weight gain, it is recommend to growth lambs in collective creep feeding using pelleted diets.